Differences in the effects of intravenous inhalational anesthesia and total intravenous anesthesia on the systemic traumatic response after laparoscopic cholecystectomy - Jun-Ping Li (Journal of Hainan Medical University, 2017)
Objective: To study the effect of intravenous inhalational anesthesia under monitoring on systemic traumatic response after laparoscopic cholecystectomy. Methods: A total of 80 cases of patients with chronic cholecystitis who received laparoscopic cholecystectomy in our hospital between June 2016 and October 2016 were collected and divided into the control group who accepted total intravenous anesthesia and the observation group who accepted intravenous inhalational anesthesia after the anesthesia methods were reviewed. 6 h, 12 h and 24 h after operation, the RIA method was adopted to determine the serum contents of pain mediators, enzyme-linked immunosorbent assay (ELISA) was used to determine serum levels of inflammatory factors and stress hormones, and auto-coagulation analyzer was used to detect the plasma contents of coagulation function indexes. Results: 6 h, 12 h and 24 h after operation, serum pain mediators 5-HT, β-EP and NPY levels of observation group were lower than those of control group, inflammatory factors hs-CRP, IL-6, IL-8 and TNF-α levels were lower than those of control group, and stress hormones Cor, ALD and NE levels were lower than those of control group; plasma coagulation function indexes TXB2, D-D and PLT levels of observation group were lower than those of control group. Conclusion: Intravenous inhalational anesthesia under monitoring can reduce the systemic traumatic reaction after laparoscopic cholecystectomy and has positive clinical significance.